2021
DOI: 10.1186/s13567-021-01010-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel chicken two-dimensional intestinal model comprising all key epithelial cell types and a mesenchymal sub-layer

Abstract: The intestinal epithelium plays a variety of roles including providing an effective physical barrier and innate immune protection against infection. Two-dimensional models of the intestinal epithelium, 2D enteroids, are a valuable resource to investigate intestinal cell biology and innate immune functions and are suitable for high throughput studies of paracellular transport and epithelial integrity. We have developed a chicken 2D enteroid model that recapitulates all major differentiated cell lineages, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…The analysis of the 2260 upregulated DEGs identified in 1-week-old M cells compared to IFE cells found that 13 of the 28 genes, originally identified by Nakato et al 21 , were represented in our dataset (Supplementary Table 1 ). However, of the missing genes, such as CLU and ANXA10, have been implicated in mammalian and chicken M cell biology 21 , 24 , 27 while genes not present in our DEG dataset, such as FLI1 , CXCR4 and VIM, implied that our enrichment approach excluded immune cells and fibroblasts 28 , 29 .…”
Section: Resultsmentioning
confidence: 91%
“…The analysis of the 2260 upregulated DEGs identified in 1-week-old M cells compared to IFE cells found that 13 of the 28 genes, originally identified by Nakato et al 21 , were represented in our dataset (Supplementary Table 1 ). However, of the missing genes, such as CLU and ANXA10, have been implicated in mammalian and chicken M cell biology 21 , 24 , 27 while genes not present in our DEG dataset, such as FLI1 , CXCR4 and VIM, implied that our enrichment approach excluded immune cells and fibroblasts 28 , 29 .…”
Section: Resultsmentioning
confidence: 91%
“…The aim of this study was to disentangle the contribution of avian intestinal epithelial cells and lamina propria cells to STm infection using unique enteroid culture models. In contrast to mammalian enteroids or intestinal organoids, the inner core of chicken 3D enteroids consists of cells present in a lamina propria including T and B cells, natural killer cells, macrophages, dendritic cells (DC) and heterophils (Nash et al, 2021;Nash et al, 2023), whereas few intraepithelial leukocytes are present in chicken 2D enteroids (Orr et al, 2021). Intestinal epithelial cells are equipped with pattern recognition receptors, such as TLRs, that initiate inflammatory responses in response to pathogen-associated molecular patterns if the epithelial barrier is breached.…”
Section: Discussionmentioning
confidence: 99%
“…For each independent culture, the intestines from five embryos were pooled. For the generation of 3D enteroids, the villi were released from the tissue as previously described (Nash et al, 2021) For 2D enteroid generation, freshly isolated intestinal villi were enzymatically digested with Accutase (TFS) as previously described (Orr et al, 2021). To remove the majority of the fibroblasts, cells were resuspended in FOM media supplemented with 1X N2 supplement (TFS), 100 ng/mL human (hu) epidermal growth factor (huEGF, TFS), 10 µM CHIR 99021 (Stratech Scientific), 10 µM Y27632 (Stem Cell Technologies) and 100 nM LDN193189 (Cambridge Bioscience).…”
Section: Generation Of Chicken 2d and 3d Enteroidsmentioning
confidence: 99%
See 2 more Smart Citations